Factors influencing the clinical outcome of preimplantation genetic testing for polycystic kidney disease. Issue 5 (30th March 2019) - Berckmoes, V; Verdyck, P; De Becker, P; De Vos, A; Verheyen, G; Van der Niepen, P; Verpoest, W; Liebaers, I; Bonduelle, M; Keymolen, K; De Rycke, M
Abstract: STUDY QUESTION: What are the factors influencing the success rate for couples undergoing preimplantation genetic testing (PGT) for polycystic kidney disease (PKD)? SUMMARY ANSWER: In our study cohort, the live birth delivery rate is significantly associated with female age while the male infertility accompanying autosomal dominant PKD (ADPKD) does not substantially affect the clinical outcome. WHAT IS KNOWN ALREADY: While women with ADPKD have no specific fertility problems, male ADPKD patients may present with reproductive system abnormalities and infertility. STUDY DESIGN, SIZE, DURATION: This retrospective cohort study involves 91 PGT cycles for PKD for 43 couples (33 couples for PKD1, 2 couples for PKD2 and 8 couples for autosomal recessive PKD (ARPKD)) from January 2005 until December 2016 with follow-up of transfers until end of 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Sixteen single-cell clinical tests for PKD based on multiplex PCR of short tandem repeat markers, with or without a specific mutation were developed and applied for diagnosis of 584 Day 3 cleavage stage embryos. In 18 couples, the male partner was affected with ADPKD (=Group A) and 12 of them had a documented infertility status. Group A underwent 52 cycles to oocyte retrieval. For 18 other couples, the female partner was affected with ADPKD (=Group B) and four male partners from this group had a documented history of infertility. This group underwent 31 cycles to OR. MAIN RESULTS AND THE ROLE OF CHANCE: Genetic analysis resulted in 545 embryos (93.3%) with a diagnosis, of which 215 (36.8%) were genetically transferable. Transfer of 74 embryos in 53 fresh cycles and of 34 cryopreserved embryos in 33 frozen–warmed embryo transfer cycles resulted in a live birth delivery rate of 38.4% per transfer with 31 singleton live births, two twin live births and one ongoing pregnancy. The observed cumulative delivery rate was 57.8% per couple after five treatment cycles. Thirty cryopreserved embryos still remain available for transfer. The clinical pregnancy rate per transfer (fresh + frozen; 45.9% in group A versus 60.0% in group B, P < 0.05) and the live birth delivery rate per transfer (fresh + frozen; 27.0% in group A versus 42.9% in group B, P < 0.05) was significantly lower for couples with the male partner affected with ADPKD compared with couples with the female partner affected with ADPKD. However, a multivariate logistic regression analysis showed that only female age was associated with live birth delivery rate (odds ratio = 0.87; 95% CI: 0.77–0.99; P = 0.032). LIMITATIONS, REASONS FOR CAUTION: This study is based on retrospective data from a single centre with Day 3 one-cell and two-cell biopsy. Further analysis of a larger cohort of PKD patients undergoing PGT is required to determine the impact of male infertility associated with ADPKD on the cumulative results. WIDER IMPLICATIONS OF THE FINDINGS: Knowledge about factors affecting the clinical outcome after PGT can be a valuable tool for physicians to counsel PKD patients about their reproductive options. Males affected with ADPKD who suffer from infertility should be advised to seek treatment in time to improve their chances of conceiving a child. STUDY FUNDING/COMPETING INTEREST(S): No funding was obtained. There are no competing interests to declare. TRIAL REGISTRATION NUMBER: Not applicable.